AWANGARDOWY „SŁOŃ TRĄBALSKI”. O NOWATORSTWIE WIERSZY JULIANA TUWIMA - Woźniak, Monika (Prace Polonistyczne, 2020)
The connection between the avant-garde and Polish children’s literature may seem somewhat tenuous, since the former was generally considered, not without a reason, secondary and peripheral to mainstream literature. For a long time, Polish children’s literature, whose main aim was to serve educational and patriotic purposes, was perceived in such a way, which makes Julian Tuwim’s works even more exceptional. Tuwim revolutionized the traditional approach to poetry for children and created a literary style that was by no means inferior to experimental literature for adults. This article analyses two aspects of the innovativeness of Tuwim’s poetry: a) a radical departure from the former literary patterns and conventions that were typical of works for children and b) a creative development of the experiments first introduced by representatives of such avant-garde movements as Futurism and Surrealism.